LOSS ANALYSIS IN BREAD PRODUCTION PROCESS USING MATERIAL FLOW COST ACCOUNTING TECHNIQUE: Received: 26th June 2023; Revised: 03rd October 2023, 27th October 2023; Accepted: 03rd November 2023 - Yoddee, Bunyaporn; Chompu-inwai, Rungchat (MATTER: International Journal of Science and Technology, 2023)
The case study factory manufactures a range of bread and bakery products for distribution in the North of Thailand. Losses from the production process were recently discovered, which besides being lost costs, also impacted the environment. This research is conducted under the concept of Material Flow Cost Accounting (MFCA) to analyze the losses from each process of the case study bread factory. This is to pinpoint where most of the losses occur and suggest methods for future improvement. This research is conducted with the principle of Plan Do Check Action (PDCA). The “Plan” was to determine a target product, which in this case was raisin bread, as it accounted for the largest proportion of production. Subsequently, a study was conducted of the production process, and a scope under the “Do” stage of the procedure was determined. Input and output factors were identified for each Quantity Center (QC) in both physical units and financial units. Subsequently at the “Check” stage, an analysis of costs was conducted for each QC with the MFCA technique. This was divided into positive product, meaning costs generating revenue, and which were manifest in the product, and negative product, which were costs not generating revenue and were losses from each production stage. Finally, at the “Action” stage, negative products were ranked using Pareto diagram to identify and evaluate opportunities for improvement. The research found that the total costs to produce one production lot of raisin bread were 2,935.55 THB, which were divided into materials costs of 2,270.79 THB (77.35%), system costs of 500.30 THB (17.04%) and energy costs of 164.46 THB (5.60%). Overall, negative product was 25.19%, of which negative product in material costs was 19.41%. This negative product was wastage and losses from dough and fillings being deposited in the machinery, and the failure of packaging films when they were being installed in the packing machine. It was also found that negative materials costs arose maximum in the QC of packing. The conclusions from this research are that it has informed about losses arising in the production process and evaluated them in the form of costs, which should help in proposing methods to reduce this wastage in the future.